Purpura of the Face and Neck: An Atypical Clinical Presentation Revealing a Hepatosplenic T Cell Lymphoma - François Kuonen (Case Reports in Dermatology, 2014)
Background: Hepatosplenic T cell lymphoma (HSTL) is a rare but very aggressive peripheral T cell lymphoma whose initial silent clinical presentation unfortunately delays the diagnosis and worsens the prognosis of patient survival. Efforts should be aimed at early recognition and treatment. Methods: We describe a case of a 62-year-old woman who presented at our clinic with a non-palpable purpuric eruption of the face. Investigations revealed thrombocytopenia with hepatosplenomegaly, which showed rapid progression together with accentuation of the purpura. Two months later, a bone marrow biopsy revealed the diagnosis of a HSTL. Results: The patient received six cycles of CHOP chemotherapy (vincristine, cyclophosphamide, doxorubicin, methylprednisolone) followed by a well-tolerated autologous bone marrow graft. Normalization of the platelet count resulted in regression of the purpuric rash. Conclusion: To our knowledge, this is the first report of a facial thrombocytopenic purpura as the inaugural symptom of HSTL. It emphasizes the privileged position of the dermatologist for early recognition of potentially lethal HSTL.